Molecular Mechanism of Long Noncoding RNA SNHG14 in Osteogenic Differentiation of Bone Marrow-Derived Mesenchymal Stem Cells through the NEDD4L/FOXA2/PCP4 Axis - Han Wang; Mingxing Fan; Yan An; Da He (Hindawi Limited, 2023)
Bone marrow-derived mesenchymal stem cells (BMSCs) have a superior potential of osteogenic differentiation (OD) and a promising stem cell type to treat bone defects. This study sought to investigate the molecular mechanism of long noncoding RNA small nucleolar RNA host gene 14 (SNHG14) in OD of BMSCs. Western blot analysis or RT-qPCR showed that SNHG14, neural precursor cell expressed developmentally downregulated 4-like (NEDD4L), and Purkinje cell protein 4 (PCP4) were upregulated whereas forkhead box A2 (FOXA2) was declined in OD of BMSCs. RT-qPCR and cell staining showed that SNHG14 downregulation repressed OD of BMSCs, as manifested by reductions in osteopontin and osteocalcin levels, the mineralization degree, and alkaline phosphatase activity. RNA/Co/chromatin immunoprecipitation and dual-luciferase assays and determination of mRNA stability and ubiquitination level showed that SNHG14 bound to human antigen R improves NEDD4L mRNA stability and expression, further promoted FOXA2 ubiquitination to inhibit FOXA2 expression, and then reduced FOXA2 enrichment on the PCP4 promoter to upregulate PCP4 transcription. Functional rescue experiments showed that the overexpression of NEDD4L or PCP4 and knockdown of FOXA2 both attenuated the inhibition of SNHG14 downregulation on OD of BMSCs. Overall, our findings suggested that SNHG14 promoted OD of BMSCs through the NEDD4L/FOXA2/PCP4 axis.